Impact of first‐line infliximab on the pharmacokinetics of second‐line vedolizumab in inflammatory bowel diseases. Issue 6 (1st July 2019) - Liefferinckx, Claire; Verstockt, Bram; Gils, Ann; Tops, Sophie; Van Moerkercke, Wouter; Vermeire, Severine; Franchimont, Denis
Abstract : Background: Very little is known about the impact of the wash‐out period on the pharmacokinetics of a second‐line biologic. Objective: The objective of this article is to explore the impact of two different wash‐out periods on the pharmacokinetics of vedolizumab and infliximab. Methods: Patients switching from infliximab to vedolizumab were retrospectively identified. The population was divided into two groups according to wash‐out period: <6 weeks or >6 weeks. Vedolizumab and infliximab trough levels (TLs) were determined and correlated with clinical and biological outcomes. Results: A total of 71 inflammatory bowel disease patients were included. At week 6, in patients previously treated with infliximab, median vedolizumab TLs were 21.9 µg/ml and 24.9 µg/ml for the <6 weeks and >6 weeks wash‐out period, respectively ( p  = 0.31), whereas median residual infliximab TLs were 0.5 µg/ml and 0 µg/ml ( p  = 0.034). The rate of treatment discontinuation was similar ( p  = 0.64), and the infectious events were six and two for the <6 weeks and >6 weeks wash‐out period, respectively ( p  = 0.12) by week 30. Conclusions: This study suggests clinicians may not need to be concerned about the impact of wash‐out period on the pharmacokinetics of the second‐line biologic when switching infliximab to vedolizumab. More data are required on the impact of wash‐out period on safety.